Feasibility of banana (Musa sapientum) trunk biofibres for treating kitchen wastewater - Daud, Zawawi; Suhani, Noorain; Radin Mohamed, Radin Maya Saphira; Awang, Halizah (Technoscience Publications, 2017)
Kitchen wastewater that is discharged to the environment is one of the contributing factors to water pollution in Malaysia and other developing countries. Various techniques have been employed to remove the pollutants namely, physical, chemical and biological treatment. Biosorption is one of the biological treatments that has emerged as a new technology for the removal and recovery of pollutants, which is more environmental friendly. This study focuses on the effectiveness of the kitchen wastewater treatment systems using low-cost natural fibre of banana trunk (Musa sapientum) as biofibre to remove COD, ammonia nitrogen, suspended solids, turbidity, colour, and oil and grease from kitchen wastewater. The optimum adsorption capacities of banana trunk biofibres were investigated under several conditions, namely, pH, absorbent dosage, speed and contact time. The optimum pH was found to be 6. The experimental results obtained were satisfactory at a dosage of 2 g at 150 rpm. The banana fibres show satisfactory COD removal of 88%, ammonia nitrogen of 84%, suspended solids of 83%, turbidity of 75%, the colour of 67% and oil and grease of 68% respectively. Maximum removal was achieved at 2 hours contact time. The study reveals that the banana fibres could be acceptable for efficient removal of organics and nutrients present in the kitchen wastewater.